José María Arguedas as a representative of Quechua culture: Analysis of the novel The Zorro Above and the Zorro Below - Mroz, Marcin (1981)
José María Arguedas was born in Andahuaylas, department of Apurímac, in 1911, to a mestizo mother and a white father. His mother died when he was three years old. The father practiced the legal profession in several provinces. For a period the boy lived with his stepmother and then ran away to an uncle's ranch. Mistreated by relatives, he became attached to the Indians. Until the age of nine, he practically spoke Spanish to us. Then, picked up by his father, he walked with him through more than twenty towns until, in 1931, he entered the Faculty of Letters of the University of San Marcos. His first short stories are autobiographical in nature, describing the towns in the Peruvian highlands where he spent his childhood. His interest in the Quechua people is also manifested in his later works on ethnology and in the mature period of his literary creation.